Relationship between innovation climate and entrepreneurial attitude in International Business and Administration students: a study case about the Universidad Continental de Peru - Ramirez-Lazo, Oscar Horacio (2025)
The economic growth of a society is mainly due to the entrepreneurship and innovation developed by its members, and universities play a fundamental role in promoting entrepreneurship and spaces where innovation is developed. Peru is one of the countries with the greatest intention to undertake in Latin America and the world, but it is also characterized by a high rate of discontinuity in entrepreneurship. Therefore, the objective of this study is to determine the level of influence of the innovation climate on the entrepreneurial attitude of students studying Business Administration and International Business at Universidad Continental through a quantitative study of 219 students between 18 and 24 years of age and both sexes. The student’s Entrepreneurial Attitude Scale and the Open Innovation Climate Scale were used. The following results were obtained by applying these instruments: the greater the innovation climate, the greater the entrepreneurial attitude, besides, a degree of influence cannot be considered as representative between the dimensions of each variable. The comparative results between the first and fifth year students showed that the most notable difference is seen in the final year students due to the negative relationship between the outward dimensions’ focus and innovation, and flexibility with some dimensions of the entrepreneurial attitude variable. It was not identified how representative the degree of influence between both variables is. We conclude that students perceive the level of innovation and flexibility, as well as reflexivity, as high, but as low, depending on the outward focus that the university presents; In relation to the entrepreneurial attitude, a representative degree of influence was not identified between the dimensions of each variable.